Pengembangan Kualitas Diri Melalui Pengelolaan Manajemen Sumber Daya Manusia - Dita Rachmawati,; Sari Sukmawati, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2023)
For the success of an organization or business, competent human resources are unquestionably necessary. Possessing quality resources may aid in the organization's improved operation. In order to obtain quality human resources, management is also necessary for human resource management. In order to develop quality human resources, this author teaches how to manage human resources. According to the study's findings, human resource management may be used to improve the quality of human resources. The administration here is concerned with cultivating human traits. Recruitment, selection, and placement are the three phases that must be completed in order to gain excellent human resources. We are concentrating on other qualities in these three stages as well, such as honesty, responsibility, trust, intellect, and attitude, in addition to competence. Focusing on improving the caliber of human resources is the next step after completing these three phases. Human resource development is measured by three factors: motivation, personality, and skills. The most crucial element of human resource management is this.